Art workers in Colombia: Characteristics, symbolic consumption and social identity - Ruby Lorena Carrillo Barbosa; Alfredo Guzmán Rincón (European Research on Management and Business Economics (ERMBE), 2022)
Purpose To explore the characteristics of Art Workers in Colombia, expressed in terms of lifestyles and consumption practices, as well as the relationship between symbolic consumption and the social identity of the group. Design/methodology/approach For this quantitative study, the instrument called "Lifestyles and consumption practices", designed by the Konrand Lorentz University Foundation, was applied along with the incorporation of two new sections which evaluate symbolic consumption and social identity. The sample was intentional and represented 160 people, 80 of them corresponding to the Art Workers category and the other 80 to the Non-Art Workers category (mirror sample). Findings It is observed that Art Workers in Colombia represent a social group with unique characteristics (lifestyles and consumption practices) looking for symbols in the products which allow them to relate to their counterparts in order to strengthen their sense of belonging to the social group. Originality/Value This work contributes the literature of marketing with a new perspective of the Art Workers which separates them from their role as instruments of advertising strategies by linking them as consumers.
Keywords: J44; Z11; 650; Art workers; Lifestyles and consumption practices; Social identity; Symbolic consumption